The relationship between self-efficacy with environmental literacy based on students’ academic level - Rahmawati, Fitri Nur; Astutik, Fuji; Akmalia, Hafidha Asni (Universitas Negeri Jakarta, 2025)
The aim of the research is to find out the relationship between environmental literation and self-efficacy based on students’ academic level of the 10th grade of SMA Negeri 1 Limbangan on the learning material of ecosystem. Correlational study became the core of the research. The research was conducted in March 2024. The type of the research is correlational with the sample of 192 students, sampled using the purposive sampling technique, proved by average score of daily test. Data collection technique using a non-test instrument in form of self-efficacy questionnaire as well as an environmental literacy essay test. Research instrument used is a self-efficacy questionnaire consists of 10 statements to measure environmental literacy covering 25 questions. Data analysis using product moment correlation. The result obtained correlation coefficient between self-efficacy with environmental literacy showed the value of 0.616, ranged between 0.60 and 0.799, enough to show the strong correlation between both variables. The result of the research showed that there is a strong relationship between academic level with environmental literacy with the correlation coefficient as high as 0.40 – 0.599. The analysis concluded that there is a positive relationship between self-efficacy and environmental literacy based on the academic level.